Test the impact of elements of strategic intelligence on the effectiveness of decision making - Osman, Muzmal Ali Mohamed (Journal of Economic, Administrative and Legal Sciences, 2017)
The study aimed to test impact of elements of strategic intelligence on the making effectiveness of decisions – Dammam – Saudi Arabia , and stand over the importance attached by this institution to strategic  intelligence and its elements of where (foresight – strategic vision – motivate employees – strategic alliances – systemic thinking  ) and its impact on effective decision  making  and we have been using descriptive and analytical method and we was design a questionnaire to collect data for the study from top administration and executive management , and it has been distributed (55) questionnaires and it was retrieved (50) questionnaires , it has been using amount of statistical methods in the study like arithmetical average , standard deviation , Cronbach's alpha , coefficient analysis , Pearson's correlation coefficient and regression analysis . The study has been reached to that there is statistically significant correlation between the elements of strategic intelligence (independent variables) and effective decision making (dependent variables),the study also presented some of a recommendations, the most important is  : attention of strategy intelligence because it is effect of decision making , and make strategic intelligence part of establishment culture , in addition to development and evolution elements of strategic intelligence , because it is effects on decision inside and outside of the establishment.
Keywords: Strategic intelligence; strategic vision; strategic alliances; thinking regulars; effective decision-making